Transexuality and transphobia in the educational system - Carvajal Villaplana, Álvaro (2018)
This paper draws from scientifc data, especially in biology and neurosciences, some insights to analyze the way transsexuality manifests itself in teenagers. Accordingly, we explore out some aspects of how the transsexual identity is formed in adolescence. We show also how sexual diﬀerentiation based on transsexuality is the motive for discrimination and violence in the school system. We try to identify some way such a system operates against and excludes transsexuals. At the end of this paper we include a summary of protocols for intervention in search of protection and promotion of the human rights of these persons. We review several studies on the case of Costa Rica between the years 2008 to 2016, and we note that there are no social researches on this important issue in the country.